2022
DOI: 10.1007/s00018-022-04277-3
|View full text |Cite
|
Sign up to set email alerts
|

RIP140 inhibits glycolysis-dependent proliferation of breast cancer cells by regulating GLUT3 expression through transcriptional crosstalk between hypoxia induced factor and p53

Abstract: Glycolysis is essential to support cancer cell proliferation, even in the presence of oxygen. The transcriptional co-regulator RIP140 represses the activity of transcription factors that drive cell proliferation and metabolism and plays a role in mammary tumorigenesis. Here we use cell proliferation and metabolic assays to demonstrate that RIP140-deficiency causes a glycolysis-dependent increase in breast tumor growth. We further demonstrate that RIP140 reduces the transcription of the glucose transporter GLUT… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Our previous study revealed an interaction between RIP140 and the hypoxia-inducible factors (HIFs) [14], also known to regulate G6PD expression [24]. Of note, hypoxia-induced G6PD expression was abolished in RIPKO MEFs (Supplementary Figure S5B), suggesting that HIF-RIP140 interplay may be involved in the regulation of G6PD by hypoxia.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Our previous study revealed an interaction between RIP140 and the hypoxia-inducible factors (HIFs) [14], also known to regulate G6PD expression [24]. Of note, hypoxia-induced G6PD expression was abolished in RIPKO MEFs (Supplementary Figure S5B), suggesting that HIF-RIP140 interplay may be involved in the regulation of G6PD by hypoxia.…”
Section: Discussionmentioning
confidence: 95%
“…However, its role in cancer metabolism remains poorly described. Our previous work has shown that RIP140 impinges breast cancer cell proliferation by blocking glycolysis through the inhibition of the glucose transporter GLUT3 expression [14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations